Cyproterone acetate acts as a disruptor of the aryl hydrocarbon receptor - Chih-Shou Chen (Nature Portfolio, 2021)
Abstract Prostate cancer is a major cause of death in males. Cyproterone acetate (CPA), the steroidal anti-androgen for part of androgen deprivation therapy, may block the androgen-receptor interaction and then reduce serum testosterone through its weak anti-gonadotropic action. In addition to CPA inducing hepatitis, CPA is known to cause liver tumors in rats also. Aryl hydrocarbon receptor (AhR) is a cytoplasmic receptor and regulates multiple physiological functions. CYP1A1 is an AhR-targeted gene. We found that CPA induced CYP1A1 expression, transcriptional activity of the aryl hydrocarbon response element (AHRE), and the nuclear localization of AhR in mouse Hepa-1c1c7 cells. However, CPA suppressed CYP1A1 mRNA expression and the transcriptional activity of AHRE in human HepG2 and MCF7 cells, and also decreased AhR ligand-induced CYP1A1 protein expression and transcriptional activity of AHRE in HepG2 cells. In summary, CPA is an AhR agonist in mouse cells, but an AhR antagonist in human cells. Accordingly, CPA potentially plays a role as an endocrine disruptor of the AhR. This study helps us to understand why CPA induces acute hepatitis, gene mutation, and many other side effects. In addition, it may trigger further studies investigating the relationships between CPA, glucocorticoid receptor and castration-resistant prostate cancer in the future.